MEASURING QUALITY OF READING MATERIALS IN ENGLISH TEXTBOOK: THE USE OF LEXICAL DENSITY METHOD IN ASSESSING COMPLEXITY OF READING MATERIALS OF INDONESIA’S CURRICULUM – 13 (K13) ENGLISH TEXTBOOK Dian Sari - Dian Sari (Universitas Bengkulu, 2016)
This research seeks to study the quality of Curriculum – 13 (K13) English textbook provided by the Government of Indonesia. This will use the senior year of high school’s textbook due to its emphasis on reading aspect. In order to assess the quality of K13 English textbook, in-depth analysis on selected reading texts will be performed by measuring their lexical density using the Castello (2008) refers to the former way as the method of calculating, which is Ure (1971) and Halliday (1985). The analysis also attempts to shed the light regarding the readability of reading texts provided in the textbook. It is important as the basis to decide whether the K13 English textbook assessed has met the aspired quality in terms of content and suitable teaching strategy to handle difficulties of the reading materials within the book. The finding revealed that higher levels of texts do not necessarily guarantee higher lexical density indexes, that is to say, the levels of texts analyzed in this study did not match the expected indexes of lexical density. This is one aspect that can be improved of the K13 English textbook.